Some approaches to classification of dictionaries in lexicography - Gordiyenko, O. V.; Гордієнко, Олена В'ячеславівна (My University, 2020)
This research was done in the field of theoretical lexicography and reflects the results of one stage of English medical terminography complex study. The work highlights some main approaches to typological classification of general and specialized dictionaries. The paper analyzes traditional typological classifications in general lexicography using a classification approach. It suggests the basic principles of classification in LSP (languages for specific purposes) lexicography of the subject area medicine. The study reveals that the basic principle of the typological classification of English medical reference works is the way of specific term(s) description: the relationship of the term with the concept and the object of description, as well as, the linguistic characteristics of the term as the element of the language for specific purposes.
Keywords: lexicography; typological classification; medical terminography; medical term; factual reference works; terminographic dictionary